Impact of bound ssRNA length on allostery in the Dengue Virus NS3 helicase - Amrein, Fernando (2023)
The presence of ATP is known to stimulate helicase activity of the Dengue Virus Non-structural protein 3 helicase (NS3h), and the presence of RNA stimulates NS3h ATPase activity, however this coupling is still mechanistically unclear. Here we use atomistic models and molecular dynamics simulations to evaluate the single-stranded RNA (ssRNA)-length dependence of the NS3h-ssRNA binding affinity and its modulation by bound ATP. Considering complexes with 7, 11, 16 and 26 nucleotides (nts), we observe that both the binding affinity and its modulation by bound ATP are augmented with increased ssRNA lengths. In models with at least 11 nts bound, the binding of ATP results in a shift from a tightly bound to a weakly bound state. We find that the weakly bound state persists during both the ADP-Pi- and ADP-bound stages of the catalytic cycle. We obtain the equilibrium association constants for NS3h binding to an ssRNA 10-mer in vitro, both in the absence and presence of ADP, which further support the alternation between tightly and weakly bound states during the catalytic cycle. The length of bound ssRNA is critical for understanding the NS3h-RNA interaction as well as how it is modulated during the catalytic cycle.